Risk factor analysis of axial symptoms after single-segment anterior cervical discectomy and fusion: A retrospective study of 113 patients. Issue 12 (December 2019) - Wang, Lin-Feng; Dong, Zhen; Miao, De-Chao; Shen, Yong; Wang, Feng
Objective: This retrospective study was performed to investigate the risk factors for axial symptoms (AS) after single-segment anterior cervical discectomy and fusion (ACDF). Methods: One hundred thirteen patients with cervical spondylosis who had undergone single-segment ACDF from January 2012 to December 2015 were divided into those with and without AS (n = 34 and n = 79, respectively). Clinical data and radiological evaluation results were recorded. Results: The occurrence rate of AS was 30.1% (34/113), and the average visual analog scale score was 4.5 points. Bony fusion was achieved in all cases during follow-up. There were no differences in age, sex, disease duration, diagnostic categories, operative segment, Japanese Orthopaedic Association score, or adjacent segment degeneration. However, cervical range of motion (CROM), cervical curvature, and disc space enlargement significantly differed between the groups. Logistic regression analysis revealed that CROM, cervical curvature, and disc space enlargement were independently associated with AS. Conclusions: AS after single-segment ACDF is not rare. Disc space enlargement is a risk factor for AS, while higher CROM and lordotic cervical curvature are protective factors. Excessive or insufficient disc space enlargement could increase the incidence of AS. Maintaining CROM within the normal range and restoring cervical lordosis might help to prevent AS.